1988
DOI: 10.1111/j.1745-4549.1988.tb00071.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Processing and Storage on the Pantothenic Acid Content of Spinach and Broccoli

Abstract: Free and total pantothenic acid (FPA and TPA) in spinach and broccoli were determined at various processing stages. Steam‐blanching resulted in greater TPA retention thatn water‐blanching. Spinach retained 36% TPA activity after water‐blanching compared with 87% retention after steam‐blanching. Similar trends were noted for TPA loss during blanching of broccoli. Canning of water‐blanched spinach resulter in a further significant loss (α= 0.05) of TPA. TPA was stable in canned spinach and frozen spinach. Frozen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 14 publications
1
7
0
Order By: Relevance
“…The adequate intake of pantothenic acid is set at 2-4 mg/day for children (27). In the past, the studies have concentrated on processing effects and the storage stability of legumes, meat, and milk powders (29)(30)(31)(32)(33)(34)(35)(36)(37). In further studies, Burger et al (38) and Schroeder et al (39) analyzed pantothenic acid contents in various fruits and also fruit juices after deep temperature storage.…”
Section: Introductionmentioning
confidence: 99%
“…The adequate intake of pantothenic acid is set at 2-4 mg/day for children (27). In the past, the studies have concentrated on processing effects and the storage stability of legumes, meat, and milk powders (29)(30)(31)(32)(33)(34)(35)(36)(37). In further studies, Burger et al (38) and Schroeder et al (39) analyzed pantothenic acid contents in various fruits and also fruit juices after deep temperature storage.…”
Section: Introductionmentioning
confidence: 99%
“…Steaming, boiling, baking, and frying of potatoes with the peel bring on pantothenic acid losses of 10% in all cases, but the losses might reach 30% in peeled potatoes when boiled [ 70 , 73 ]. In addition, in vegetables, boiling and steaming usually causes declines of 10% in the total dish, and those of 30–40% and 15%, respectively, in vegetables alone [ 70 , 73 , 98 , 709 ]. Stewing, frying, and baking lessen pantothenic acid amounts in vegetables by 10% [ 70 , 73 ].…”
Section: Pantothenic Acid—vitamin Bmentioning
confidence: 99%
“…Pantothenic acid losses of 24–67% in legumes during boiling are influenced by the pre-soaking method and cooking times [ 74 , 710 , 711 ] Boiling of rice results in a decrease of 59–66% in pantothenic acid content [ 99 ]. That is why steaming is preferred to boiling, in particular, when cooked vegetables are eaten without cooking liquids [ 70 , 98 , 709 , 712 ]. Poached, boiled, and fried eggs lose, due to cooking, 4%, 7%, and 9% of their pantothenic acid, respectively [ 107 ].…”
Section: Pantothenic Acid—vitamin Bmentioning
confidence: 99%
“…In a study conducted by Cheng and Eitenmiller (1988), the total amount of pantothenic acid in fresh broccoli was determined as 4.92-9.34 ppm and the amount of pantothenic acid in the steam cooked broccoli samples was determined to be higher than that in the boiled samples. Kramer (1979) and Kramer et al (1979) have reported frozen broccoli to score higher values in terms of thiamine and ascorbic acid content as well as sensory properties than the canned broccoli.…”
Section: Introductionmentioning
confidence: 99%
“…The green sprouts of broccoli might be put into market for consumption as frozen and canned food in addition to being freshly consumed. The remains that are left in the field are used for feeding the livestock (Desouzas and Eitenmiller, 1986;Cheng and Eitenmiller, 1988).…”
Section: Introductionmentioning
confidence: 99%